Cervical intraepithelial neoplasia grade 2/3: development during pregnancy and postpartum - Stübs, Frederik; Mergel, F.; Koch, M. C.; Dietl, Anna; Schulmeyer, Carla; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Gaß, Paul; Mehlhorn, G. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Cervical intraepithelial neoplasia grade 3: development during pregnancy and postpartum - Stübs, Frederik; Mergel, Franziska; Koch, Martin; Dietl, Anna; Schulmeyer, Carla; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Gaß, Paul; Mehlhorn, Grit (Archives of Gynecology and Obstetrics, 2022)
Purpose: The aims of the present study were to evaluate the development of untreated cervical intraepithelial neoplasia (CIN) 3 during pregnancy and to assess persistence, progression, and regression rates postpartum to identify factors associated with regression. Methods: In a tertiary gynecology and obstetrics department, a total of 154 pregnant women with CIN 3 were treated in the dysplasia unit. The follow-up findings were analyzed retrospectively on the basis of histological, cytological, and human papillomavirus (HPV) testing of 154 pregnant women confirmed as having CIN 3 in colposcopically guided biopsies. Results: The rates of persistence, regression, and progression of CIN 3 in these women were 76.1%, 20% and 3.2%, respectively. Data for the delivery mode was available for 126 women. The rate of regression was almost twice as high with vaginal delivery as with cesarean section, at 27.4 vs. 15.2%, whereas the rate of progression was lower with vaginal delivery, at 2.7 vs. 6.5%. Conclusion: The rate of persistence of CIN observed in this study is comparable to that reported in other studies. The study provides strong evidence for greater regression among women who have vaginal deliveries. Careful work-up is recommended postpartum for this group of women in order to rule out persistent CIN 3 or invasive disease.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Cervical dysplasia; High-grade squamous intraepithelial lesion (HSIL); Mode of delivery; Pregnancy; Treatment

Concordance Rate of Colposcopy in Detecting Cervical Intraepithelial Lesions - Stübs, Frederik; Dietl, Anna; Behrens, Annika; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Mehlhorn, Grit; Schulmeyer, Carla; Gaß, Paul; Koch, Martin C. (Diagnostics, 2022)
Background: The purpose of this research is to estimate the rate of concordance, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of colposcopy for high-grade squamous lesions and carcinomas (HSIL+). Methods: We conducted a retrospective study of colposcopies performed in the certified Dysplasia Unit in Erlangen between January 2015 and May 2022 (7.5 years). The colposcopic findings were correlated with biopsies obtained during examinations or surgery. Cases without histology were excluded. The primary outcome was the rate of concordance between the colposcopic and histological findings in relation to the type of transformation zone (TZ), examiner's level of experience and age of the patients. Results: A total of 4778 colposcopies in 4001 women were analyzed. The rates of concordance for CIN I/LSIL, CIN II/HSIL, CIN III/HSIL, and carcinoma were 43.4%, 59.5%, 78.5%, and 53.9%, respectively. The rate of concordance was lowest for TZ3 and highest for colposcopists with more than 10 years' experience. Conclusions: Colposcopy is an important, feasible, and effective method. Careful work-up needs to be performed for women with TZ3 who are over 35 years old, as they are at the highest risk of being misdiagnosed. The highest concordance for detecting HSIL+ was seen for colposcopists with >10 years' experience.
CRIS-Team WoS Importer:2022-11-11

COVID-19 effects on the kidney. - Amann, Kerstin Ute; Boor, P.; Wiech, T.; Singh, Jeeshan; Vonbrunn, Eva; Knöll, Antje; Hermann, Maike; Büttner-Herold, Maike; Daniel, Christoph; Hartmann, Arndt (Pathologe, 2021)
Apart from pulmonary disease, acute kidney injury (AKI) is one of the most frequent and most severe organ complications in severe coronavirus disease 2019 (COVID-19). The SARS-CoV‑2 virus has been detected in renal tissue. Patients with chronic kidney disease (CKD) before and on dialysis and specifically renal transplant patients represent a particularly vulnerable population. The increasing number of COVID-19 infected patients with renal involvement led to an evolving interest in the analysis of its pathophysiology, morphology and modes of virus detection in the kidney. Meanwhile, there are ample data from several autopsy and kidney biopsy studies that differ in the quantity of cases as well as in their quality. While the detection of SARS-CoV‑2 RNA in the kidney leads to reproducible results, the use of electron microscopy for visualisation of the virus is difficult and currently critically discussed due to various artefacts. The exact contribution of indirect or direct effects on the kidney in COVID-19 are not yet known and are currently the focus of intensive research.
EVALuna2:421391

COVID-19 effects on the kidney - Amann, Kerstin Ute; Boor, P.; Wiech, T.; Singh, Jeeshan; Vonbrunn, Eva; Knöll, Antje; Hermann, Maike; Büttner-Herold, Maike; Daniel, Christoph; Hartmann, Arndt (Pathologe, 2021)
Apart from pulmonary disease, acute kidney injury (AKI) is one of the most frequent and most severe organ complications in severe coronavirus disease 2019 (COVID-19). The SARS-CoV-2 virus has been detected in renal tissue. Patients with chronic kidney disease (CKD) before and on dialysis and specifically renal transplant patients represent a particularly vulnerable population. The increasing number of COVID-19 infected patients with renal involvement led to an evolving interest in the analysis of its pathophysiology, morphology and modes of virus detection in the kidney. Meanwhile, there are ample data from several autopsy and kidney biopsy studies that differ in the quantity of cases as well as in their quality. While the detection of SARS-CoV-2 RNA in the kidney leads to reproducible results, the use of electron microscopy for visualisation of the virus is difficult and currently critically discussed due to various artefacts. The exact contribution of indirect or direct effects on the kidney in COVID-19 are not yet known and are currently the focus of intensive research.
CRIS-Team WoS Importer:2021-02-19

Cytology and High-Risk Human Papillomavirus Test for Cervical Cancer Screening Assessment - Stübs, Frederik; Koch, Martin C.; Dietl, Anna; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Mehlhorn, Grit; Schulmeyer, Carla; Gaß, Paul (Diagnostics, 2022)
Background: A new nationwide screening strategy was implemented in Germany in January 2020. No data are available for women referred to certified dysplasia units for secondary clarification after primary diagnosis by a local physician. We therefore investigated combined testing with Papanicolaou smears and high-risk human papillomavirus (hrHPV) and compared the data with the final histological findings. Methods: Between January 2015 and October 2020, all referred women who underwent colposcopy of the uterine cervix in our certified dysplasia unit were included. Cytology findings were classified using the Munich III nomenclature. Results: A total of 3588 colposcopies were performed in 3118 women, along with Pap smear and hrHPV co-testing, followed by histology. Women with Pap II-p (ASC-US) and a positive hrHPV co-test had a 22.4% risk for cervical intraepithelial neoplasia (CIN) 3/high-grade squamous intraepithelial lesion (HSIL). The risk of CIN 3/HSIL was 83.8% in women with Pap IVa-p (HSIL) and a positive hrHPV co-test. A positive hrHPV co-test increased the risk for HSIL+ (OR 5.942; 95% CI, 4.617 to 7.649; p < 0.001) as compared to a negative hrHPV co-test. Conclusions: The accuracy of Pap smears is comparable with the screening results. A positive hrHPV test increases the risk for HSIL+ fivefold. Colposcopy is necessary to diagnose HSIL+ correctly.
CRIS-Team WoS Importer:2022-08-12

Cytology and HPV Co-Testing for Detection of Vaginal Intraepithelial Neoplasia: A Retrospective Study. - Stübs, Frederik; Dietl, Anna; Koch, Martin C.; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Mehlhorn, Grit; Beckmann, Matthias; Schulmeyer, Carla; Heindl, Felix; Emons, Julius; et al. (Cancers, 2023)
(1) Background: Vaginal intraepithelial neoplasia (VaIN) is a rare premalignant disease caused by persistent human papillomavirus (HPV) infection. Diagnosing VaIN is challenging; abnormal cytology and positive HPV tests are usually the first signs, but published data on their accuracy for detecting it are rare and contradictory. The aim of this study is to compare the results of hrHPV and cytology co-testing with the histological findings of the vagina. (2) Methods: In the certified Dysplasia Unit at Erlangen University Hospital, cytology and HPV samples from the uterine cervix or vaginal wall after hysterectomy were obtained between 2015 and 2023 and correlated with histological findings in biopsies from the vaginal wall. Women without vaginal biopsy findings or concomitant cervical disease were excluded. (3) Results: In all, 279 colposcopies in 209 women were included. The histological results were: benign (n = 86), VaIN I/vLSIL (n = 116), VaIN II/vHSIL (n = 41), VaIN III/vHSIL (n = 33), and carcinoma (n = 3). Accuracy for detecting VaIN was higher in women with previous hysterectomies. Positive HPV testing during colposcopy increased the likelihood for VaIN II/III/vHSIL threefold. The detection rate for VaIN III/vHSIL was 50% after hysterectomy and 36.4% without hysterectomy. (4) Conclusions: Women with risk factors for VaIN, including HPV-16 infection or prior HPV-related disease, need careful work-up of the entire vaginal wall. Hysterectomy for HPV-related disease and a history of cervical intraepithelial neoplasia (CIN) also increased the risk for VaIN II/III/vHSIL.
EVALuna2:540622

Cytology and hrHPV for cervical cancer screening assessment - Stübs, Frederik; Koch, M. C.; Dietl, Anna; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Mehlhorn, G.; Gaß, Paul; Schulmeyer, Carla (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Estimates and determinants of sars-cov-2 seroprevalence and infection fatality ratio using latent class analysis: The population-based tirschenreuth study in the hardest-hit german county in spring 2020 - Wagner, Ralf; Peterhoff, David; Beileke, Stephanie; Günther, Felix; Berr, Melanie; Einhauser, Sebastian; Schütz, Anja; Niller, Hans Helmut; Steininger, Philipp; Knöll, Antje; Tenbusch, Matthias; Maier, Clara; et al. (Viruses, 2021)
SARS-CoV-2 infection fatality ratios (IFR) remain controversially discussed with implications for political measures. The German county of Tirschenreuth suffered a severe SARS-CoV-2 outbreak in spring 2020, with particularly high case fatality ratio (CFR). To estimate seroprevalence, underreported infections, and IFR for the Tirschenreuth population aged ≥14 years in June/July 2020, we conducted a population-based study including home visits for the elderly, and analyzed 4203 participants for SARS-CoV-2 antibodies via three antibody tests. Latent class analysis yielded 8.6% standardized county-wide seroprevalence, a factor of underreported infections of 5.0, and 2.5% overall IFR. Seroprevalence was two-fold higher among medical workers and one third among current smokers with similar proportions of registered infections. While seroprevalence did not show an age-trend, the factor of underreported infections was 12.2 in the young versus 1.7 for ≥85-year-old. Age-specific IFRs were <0.5% below 60 years of age, 1.0% for age 60–69, and 13.2% for age 70+. Senior care homes accounted for 45% of COVID-19-related deaths, reflected by an IFR of 7.5% among individuals aged 70+ and an overall IFR of 1.4% when excluding senior care home residents from our computation. Our data underscore senior care home infections as key determinant of IFR additionally to age, insufficient targeted testing in the young, and the need for further investigations on behavioral or molecular causes of the fewer infections among current smokers.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Antibodies; CLIA; ELISA; Infection fatality ratio; Latent class analysis; SARS-CoV-2; Senior care homes; Seroprevalence; Smoking; Underreported infections

Evaluation of endocervical curettage (ECC) in colposcopy for detecting cervical intraepithelial lesions - Behrens, Annika; Dietl, Anna; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Mehlhorn, Grit; Koch, Martin C.; Schulmeyer, Carla; Seibold, Anja; Gaß, Paul; et al. (Archives of Gynecology and Obstetrics, 2024)
Purpose: Diagnostic challenges in colposcopy arise especially in women aged 50 or older, with postmenopausal status and transformation zone type 3 (TZ3). Endocervical curettage (ECC) is a valuable tool for diagnosing intracervical lesions. The aim of this retrospective analysis was to evaluate the use of ECC in colposcopy for detecting cervical intraepithelial lesions. Methods: A retrospective study was carried out of colposcopies performed in the certified Dysplasia Unit at Erlangen University Hospital between July 2016 and June 2023. Pap and human papillomavirus (HPV) results were correlated with the histologic findings via ECC, obtained during examinations or surgery. The primary outcome was the rate of accuracy between the colposcopic and histologic findings with regard to cytology, age of patients, and type of transformation zone (TZ). Results: A total of 429 colposcopies in 413 women with histologic samples obtained via ECC were included in the final analysis. In all, 355 women had TZ3. Among patients with TZ3, evidence of high-grade lesions and invasive carcinoma was also found in women with normal or low-grade abnormal cytology. For patients with normal colposcopic findings, cervical intraepithelial neoplasia (CIN) 2 and CIN 3/adenocarcinoma in situ (AIS) were found in 56 patients (16%), and invasive carcinoma was found in four patients (0.1%). Conclusion: This analysis suggests that ECC is a valuable tool in the diagnosis of cervical intraepithelial neoplasia, especially for patients who present with a normal colposcopy of the cervix and vagina but have either recurrent abnormal cytologic findings or high-grade abnormal cytology indicating CIN 2 +.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Cervical cancer; Cervical cancer screening assessment; Cervical intraepithelial neoplasia; Colposcopy; Cytology; Endocervical curettage

HTLV-1 associated myelopathy after renal transplantation - Goevert, Felix; Krumbholz, Andi; Witt, Karsten; Hopfner, Franziska; Feldkamp, Thorsten; Korn, Klaus; Knöll, Antje; Jansen, Olav; Deuschl, Guenther; Fickenscher, Helmut (Journal of Clinical Virology, 2015)
EVALuna2:8278

Human papilloma virus genotype distribution in women with premalignant or malignant lesions of the uterine cervix - Stübs, Frederik; Gaß, Paul; Dietl, Anna; Schulmeyer, Carla; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Koch, Martin (Archives of Gynecology and Obstetrics, 2021)
Objective: Cervical cancer is caused by persistent infection with high-risk human papillomavirus (hrHPV). Cytology-based national screening programs have reduced the incidence and mortality of cervical cancer. Different hrHPV subtypes have different carcinogenic potentials. This study evaluated the distribution of different types of hrHPV relative to age in cervical cancer and its precursor lesions. Methods: HPV testing was performed between November 2018 and February 2020 using the Abbott RealTime high-risk HPV assay on an Abbott m2000sp instrument. This assay separately detects HPV-16, HPV-18, and a pool of 12 additional hrHPV types (HPV-31, -33, -35, -39, -45, -51, -52, -56, -58, -59, -66, and -68). Results: The study included 652 women with HPV samples and biopsies of the cervix or histology samples obtained during surgery. In all, 30.8% (95% CI, 27.3–34.6%) were HPV-negative. Among HPV-positive women, HPV-16, HPV-18, and “HPV other” types were found in 33.5, 4.4, and 49.4%, respectively. Cervical intraepithelial neoplasia (CIN) 3/high-grade squamous intraepithelial lesions (HSILs) in women ≤ 34 years were positive for HPV-16 in 54.5% of cases and in those ≥ 35 years in 45.4% of cases. Among women with cervical cancer, 75.8% were infected with HPV-16 or had coinfection with HPV-16 and “HPV other”. Conclusions: HPV-16 is the most common type of hrHPV in HSIL + lesions. It is more common in women diagnosed with CIN 3/HSIL who are aged ≤ 35 and is decreasing with age. Therefore, women age ≥ 35 with persistent infection with this type of hrHPV need careful surveillance, as they are at high risk of progression to cervical cancer.
CRIS-Team Scopus Importer:2021-02-19
Keywords: Age-distribtuion of HPV; Cervical cancer; Colposcopy; HPV-distribution; HSIL

Impact of the Corona Pandemic on Cervical Cancer Screening Assessment - Stübs, Frederik; Behrens, Annika; Seibold, Anja; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Koch, Martin C.; Mehlhorn, Grit; Beckmann, Matthias; Theuser, Anna Katharin; Schulmeyer, Carla; et al. (In Vivo, 2024)
BACKGROUND/AIM: The global impact of the COVID-19 pandemic resulted in disruptions to healthcare systems throughout the world. The numbers of cytology examinations, human papillomavirus (HPV) tests, and women referred for colposcopy decreased in many countries. There have been no reports on cervical cancer screening in Germany. This study aimed to describe changes in the numbers of colposcopies, cytology examinations, HPV tests, and histological results during the pandemic compared to the pre-pandemic years in order to evaluate the impact of the COVID-19 pandemic on cervical cancer screening. PATIENTS AND METHODS: The numbers of colposcopies, cytology examinations, HPV tests, and histologic results were analyzed retrospectively for the period January 2018 to December 2022. The 2 years period before the pandemic (2018 and 2019) were compared with the 3 years period of the pandemic (2020-2022). RESULTS: In total, 6,518 colposcopies were performed in 5,579 women. The numbers of colposcopies, cytology examinations, and high-risk HPV (hrHPV) tests increased during the pandemic years. The number of biopsies per year taken was stable (range=450-554). The relative numbers of cervical intraepithelial neoplasia (CIN) III/HSIL findings were stable, while the numbers of cervical cancers identified increased slightly from 15 (6.6%) in 2018 to 22 (7.4%) in 2022. CONCLUSION: Increases in numbers of women examined and colposcopies were observed in the years 2021 and 2022 during the pandemic, in comparison to the preceding years. These also led to increases in the figures for cytology, hrHPV, histology, and operations. The onset of the pandemic occurred in the same year as a newly organized screening program started in Germany. The increases might therefore be due to the newly organized screening system.
CRIS-Team Scopus Importer:2024-03-15
Keywords: cervical cancer; cervical cancer screening; cervical dysplasia; COVID-19 pandemic; High-grade squamous intraepithelial lesion (HSIL)

Influenza A virus drift variants reduced the detection sensitivity of a commercial multiplex nucleic acid amplification assay in the season 2014/15 - Huzly, Daniela; Korn, Klaus; Bierbaum, Sibylle; Eberle, Bjoern; Falcone, Valeria; Knöll, Antje; Steininger, Philipp; Panning, Marcus (Archives of Virology, 2016)
The influenza season 2014/15 was dominated by drift variants of influenza A(H3N2), which resulted in a reduced vaccine effectiveness. It was not clear if the performance of commercial nucleic-acid-based amplification (NAT) assays for the detection of influenza was affected. The purpose of this study was to perform a real-life evaluation of two commercial NAT assays. During January-April 2015, we tested a total of 665 samples from patients with influenza-like illness using the Fast Track Diagnostics Respiratory pathogens 21, a commercial multiplex kit, (cohorts 1 and 2, n = 563 patients) and the Xpert Flu/RSV XC assay (cohort 3, n = 102 patients), a single-use cartridge system. An in-house influenza real-time RT-PCR (cohort 1) and the RealStar Influenza RT-PCR 1.0 Kit (cohort 2 and 3) served as reference tests. Compared to the reference assay, an overall agreement of 95.9 % (cohort 1), 95 % (cohort 2), and 98 % (cohort 3) was achieved. A total of 24 false-negative results were observed using the Fast Track Diagnostics Respiratory pathogens 21 kit. No false-negative results occurred using the Xpert Flu/RSV XC assay. The Fast Track Diagnostics Respiratory pathogens 21 kit and the Xpert Flu/RSV XC assay had sensitivities of 90.7 % and 100 % and specificities of 100 % and 94.1 %, respectively, compared to the RealStar 1.0 kit. Upon modification of the Fast Track Diagnostics Respiratory pathogens 21 kit, the sensitivity increased to 97.3 %. Influenza virus strains circulating during the 2014/15 season reduced the detection sensitivity of a commercial NAT assay, and continuous monitoring of test performance is therefore necessary.
EVALuna2:8334

Management of Cervical Intraepithelial Neoplasia in Pregnant Women - Stübs, Frederik; Koch, Martin C.; Dietl, Anna; Schulmeyer, Carla; Behrens, Annika; Seibold, Anja; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Gaß, Paul; et al. (Anticancer Research, 2023)
BACKGROUND/AIM: The aims of the present study were to evaluate the accuracy of colposcopic findings, investigate the way in which untreated cervical intraepithelial neoplasia (CIN) 2/3 develops during pregnancy, and identify factors associated with regression, persistence, or progression rates. PATIENTS AND METHODS: In a tertiary gynecology and obstetrics department, 655 pregnant women were seen for colposcopy. The most common reason for referral was abnormal cytology findings. The follow-up findings were analyzed retrospectively on the basis of colposcopic findings and cytological and histological tests. RESULTS: The rate of accuracy for major colposcopic findings was 89.2%. Among the colposcopic findings considered "suspicious for invasion" were invasive carcinoma in 42.9% and CIN 3 in 57.1%. The persistence of CIN 3 postpartum was 80% and the rate of progression 4.1%. The rate of regression for CIN 3 was 21.9%. For CIN 2, the rate of persistence was 37.5%, with a regression rate of 31.3%. The rate of regression was higher after vaginal delivery in comparison with caesarean section. CONCLUSION: The accuracy rate of colposcopy is comparatively high, at 89.2%. This might be because pregnant women are seen by more experienced examiners in our dysplasia unit. The rate of progression is comparable with that in other studies. Vaginal delivery increases the regression rate. The newborns' birth weight or birth week did not affect the rates of regression or persistence.
CRIS-Team Scopus Importer:2023-07-07
Keywords: cervical dysplasia; High-grade squamous intraepithelial lesion (HSIL); mode of delivery; pregnancy; treatment

PD-L1-Expression in in primary and recurrent vulvar squamous cell cancer - Stübs, Frederik; Knöll, Antje; Hartmann, Arndt; Leikauf, Leah-Sophie; Matek, Christian; John, Nelson; Häberle, Lothar; Beckmann, Matthias; Geppert, Carol-Immanuel (Gynecologic Oncology, 2025)
Background: Squamous cell vulvar carcinoma is a rare malignant disease of women. In higher tumor stages survival rates are poor. Therapy options are limited. Immunoncology plays an increasing role in the treatment of gynecology cancers. Data on the expression of PD-L1 in vulvar cancer are rare and contradictory. We sought to describe the expression of PD-L1 in VSCC in respect to the clinicopathologic characteristics of the tumor. Study design: We conducted a retrospective analysis including women with primary and recurrent vulvar cancer between 2000 and 2021. A next generation tissue micro array (ngTMA) was constructed for the analysis of PD-L1 expression. Results: In total 238 women with primary VSCC and 66 cases of local or distant recurrent vulvar cancer were included. 80 women with primary VSCC (33.6 %) had tumors with common positive score (CPS) <1 and 63 women (26.5 %) had tumors with CPS 1- < 10 and 95 women with CPS ≥10 (39.9 %). In the PD-L1 positive group the rates of p53+, groin metastasis, lymphatic invasion and tumor infiltration lymphocytes were higher as compared to PD-L1 negative (CPS <1). There was no significant influence of CPS in overall survival in addition to other prognostic factors (P = 0.13, likelihood ratio test). Conclusion: PD-L1 expression in primary vulvar cancer is associated with poorer prognosis. Hence, PD-L1 is a possible target for immune checkpoint inhibitors and women might benefit from special treatment options.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Checkpoint inhibitor; Immune oncology; PD-L1-expression; Tissue micro array; Tumor infiltrating lymphocytes; Vulvar cancer

Performance characteristics of the VERSANT hepatitis C virus RNA 1.0 (kPCR) assay - Gruener, Nico; Viazov, S.; Korn, Klaus; Knöll, Antje; Trippler, M.; Schlaak, J. F.; Gerken, G.; Roggendorf, M.; Ross, R. Stefan (International Journal of Medical Microbiology, 2015)
HCV RNA assays are of central importance for virological diagnostics and for clinical planning and monitoring of an antiviral combination treatment of chronic HCV infections. The objective of the pre-market evaluation of the VERSANT HCV RNA 1.0 Assay (kPCR) was to collect analytical performance data for this new method of HCV RNA quantification and to compare them with the high standards that exist in this context. The assay exhibited a specificity of 100%. The mean intra- and inter-assay imprecision was 14.1% and 14.6%, respectively. The detection limit was determined to be 16IU/ml (95% confidence interval: 11.9-30.6IU/ml) and consequently corresponded to the manufacturer's claims (i.e. 15IU/ml). The test exhibited linearity for all HCV genotypes in a broad range from 15 to 10(8)IU HCV RNA/ml. Hence, the kPCR assay in general is well suitable for HCV RNA determinations in clinical practice. However, in a methodological comparison, a considerable under-quantification of the concentrations of HCV genotype 2 and 3 isolates was detected. Provided that the assay's manufacturer will quickly remedy this shortcoming, the VERSANT HCV RNA 1.0 (kPCR) can be called a completely reliable technique for HCV RNA quantification in routine virological diagnostics.
EVALuna2:8266

Results of Tick-Borne Encephalitis Virus (TBEV) Diagnostics in an Endemic Area in Southern Germany, 2007 to 2022. - Steininger, Philipp; Enßer, Armin; Knöll, Antje; Korn, Klaus (Viruses, 2023)
Tick-borne encephalitis virus (TBEV) is the most important tick-transmitted neurotropic flavivirus in Europe and Asia. Our analysis aimed to investigate the contribution of TBEV-specific antibody detection by serological assays and TBEV RNA detection by real-time PCR to the diagnosis of tick-borne encephalitis (TBE). We analyzed data from 3713 patients from 16 years of laboratory TBEV diagnostics in an endemic area in Southern Germany. During this period, 126 cases of TBE were diagnosed. TBEV-specific IgM ELISA tests showed a high clinical sensitivity (96.8%) and a very high clinical specificity (99.7%). In immunocompetent patients, TBE was reliably diagnosed by detection of TBEV IgM antibodies in serum. Intrathecal TBEV IgG antibody synthesis was detected in 46 of 84 (55%) cases by analysis of paired serum and cerebrospinal fluid (CSF) samples. None of the 87 immunocompetent TBE patients tested had detectable TBEV RNA in serum or CSF. In contrast, in two TBE patients without TBEV-specific antibodies, diagnosis could only be made by the detection of TBEV RNA in CSF. Both patients had previously been treated with the B cell-depleting antibody rituximab. Therefore, in patients with CNS infection and humoral immunodeficiency, it is necessary to include TBEV PCR in the diagnostic approach.
EVALuna2:545508

SMARCB1(INI1)-deficient sinonasal basaloid carcinoma: a novel member of the expanding family of SMARCB1-deficient neoplasms - Agaimy, Abbas; Koch, Michael; Lell, Michael; Semrau, Sabine; Dudek, Wojciech; Wachter, David; Knöll, Antje; Iro, Heinrich; Haller, Florian; Hartmann, Arndt (American Journal of Surgical Pathology, 2014)
Poorly differentiated sinonasal carcinomas are a heterogenous group of aggressive neoplasms that encompasses squamous cell carcinoma including basaloid variant, lymphoepithelial carcinoma, sinonasal undifferentiated carcinoma, and neuroendocrine-type small cell carcinoma. We herein describe 3 cases of a hitherto unreported variant combining features of basaloid carcinoma with variable intermingled rhabdoid cells. Patients were 2 women (aged 28 and 35) and a man (52 y) who presented with sinonasal masses. All had advanced local disease with bone involvement (pT4). None had a history of irradiation or a family history of rhabdoid tumors. Treatment was surgery and adjuvant chemoradiation. One patient developed liver, lung, pleural, and pericardial metastases (63 mo) and is currently (70 mo) alive under palliative treatment. Another developed recurrent cervical lymph node metastases and died of disease 8.5 years later. The youngest patient was disease-free at last follow-up 7 years later. Histologic features were very similar in all 3 cases and showed intimate admixture of compact basaloid cell nests with peripheral palisading, perivascular pseudorosettes, and a few scattered rhabdoid cells. Rhabdoid cells were more extensive in the metastasis in 1 case but formed a minor inconspicuous component in the primary tumors in all cases. Striking features common to all cases were (1) basaloid "blue" appearance at low power, (2) papilloma-like exophytic component, (3) extensive pagetoid surface growth with prominent denuding features, and (4) replacement of underlying mucous glands mimicking an inverted papilloma. Clear-cut origin from benign papilloma and overt squamous differentiation were lacking. Diffuse (2) or partial (1) p16 expression was noted, but all cases lacked human papillomavirus DNA by molecular tests. In situ hybridization was negative for Epstein-Barr virus. Immunohistochemistry showed diffuse expression of pancytokeratin. CK5 and vimentin showed intermingling of CK5/vimentin basaloid and CK5/vimentin rhabdoid cells. Complete loss of nuclear SMARCB1 expression was seen in all cases including also the denuding carcinoma in situ-like surface lesions. To our knowledge, this variant of sinonasal carcinoma has not been reported before. The identical features in all 3 cases suggest a specific disease rather than a nonspecific dedifferentiated phenotype. Awareness of this rare variant and thus reporting of additional cases is necessary for defining its full morphologic and biological spectrum.
EVALuna2:6600

Stellenwert der Vakzine gegen humane Papillomaviren in der Prävention von Krebserkrankungen - Schulmeyer, Carla; Knöll, Antje; Iro, Heinrich; Müller, Susanna; Beckmann, Matthias (Onkologe, 2021)
Background: Human papillomaviruses (HPV) are the most common causes of genital viral infections. HPV infections usually heal, but can also persist and thus cause lesions of different grades. Infections with high-risk HPV types (hrHPV) 16, 18, 31, 33, 45, 52, and 58 are responsible for causing 90% of cervical cancer cases in Europe. Head and neck cancer, vaginal and vulvar cancer and their precursors, as well as penile or anal cancer may also be associated with hrHPV. Objectives: The aim of this work is to demonstrate the importance of HPV vaccines in the prevention of genital as well as head and neck cancers. Materials and methods: This work is based on a selective literature search in the PubMed database on the correlation between HPV vaccines and HPV-associated cancer. Results: HPV vaccination ensures a high level of protection against precancerous lesions and cancer of the cervix, vagina, vulva, anus, and genital warts. Conclusions: Results of HPV vaccination and its positive effects on head and neck tumors is expected within the next few decades.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Condylomata acuminata; HPV; Oropharyngeal neoplasms; Sexually transmitted diseases; Uterine cervical neoplasms

Time Trend in SARS-CoV-2 Seropositivity, Surveillance Detection- and Infection Fatality Ratio until Spring 2021 in the Tirschenreuth County—Results from a Population-Based Longitudinal Study in Germany - Einhauser, Sebastian; Peterhoff, David; Beileke, Stephanie; Günther, Felix; Niller, Hans Helmut; Steininger, Philipp; Knöll, Antje; Korn, Klaus; Berr, Melanie; Schütz, Anja; Wiegrebe, Simon; Stark, Klaus J.; et al. (Viruses, 2022)
Herein, we provide results from a prospective population-based longitudinal follow-up (FU) SARS-CoV-2 serosurveillance study in Tirschenreuth, the county which was hit hardest in Germany in spring 2020 and early 2021. Of 4203 individuals aged 14 years or older enrolled at baseline (BL, June 2020), 3546 participated at FU1 (November 2020) and 3391 at FU2 (April 2021). Key metrics comprising standardized seroprevalence, surveillance detection ratio (SDR), infection fatality ratio (IFR) and success of the vaccination campaign were derived using the Roche N-and S-Elecsys anti-SARS-CoV-2 test together with a self-administered questionnaire. N-seropositivity at BL was 9.2% (1st wave). While we observed a low new seropositivity between BL and FU1 (0.9%), the combined 2nd and 3rd wave accounted for 6.1% new N-seropositives between FU1 and FU2 (ever seropositives at FU2: 15.4%). The SDR decreased from 5.4 (BL) to 1.1 (FU2) highlighting the success of massively increased testing in the population. The IFR based on a combination of serology and registration data resulted in 3.3% between November 2020 and April 2021 compared to 2.3% until June 2020. Although IFRs were consistently higher at FU2 compared to BL across age-groups, highest among individuals aged 70+ (18.3% versus 10.7%, respectively), observed differences were within statistical uncertainty bounds. While municipalities with senior care homes showed a higher IFR at BL (3.0% with senior care home vs. 0.7% w/o), this effect diminished at FU2 (3.4% vs. 2.9%). In April 2021 (FU2), vaccination rate in the elderly was high (>77.4%, age-group 80+).
CRIS-Team Scopus Importer:2022-06-17
Keywords: case fatality ratio; elderly; infection fatality ratio; longitudinal; population-based; SARS-CoV-2; senior care homes; seroprevalence; surveillance detection ratio; vaccination

Variant morphology and random chromosomal integration of BK polyomavirus in posttransplant urothelial carcinomas - Bertz, Simone; Enßer, Armin; Stöhr, Robert; Eckstein, Markus; Apel, Hendrik; Mayr, Doris; Büttner-Herold, Maike; Gaisa, Nadine Therese; Comperat, Eva; Wullich, Bernd; Hartmann, Arndt; Knöll, Antje (Modern Pathology, 2020)
BK polyomavirus (BKPyV) causes major complications in solid organ transplant recipients but little is known about its role in the development of urothelial carcinoma (UC) during immunosuppression. Immunohistochemistry (IHC) screening for polyomavirus large T antigen (LTag) was performed in 94 micropapillary UC (MPUC), 480 unselected UC, 199 muscle invasive UC (including 83 UC with variant differentiation), 76 cases of plasmocytoid, nested and large nested UC and 15 posttransplant UC. LTag expressing UC were reevaluated regarding their histomorphological features and characterized by IHC for p53 and HER2, chromogenic in situ hybridization for HER2 and SNaPshot analysis of the TERT promoter and HRAS. Real-time PCR and next generation sequencing (NGS) were performed to search for BKPyV-DNA and for variants in the tumor and viral genomes. We detected five LTag expressing UC which were diagnosed between 2 and 18 years after kidney (n = 4) or heart (n = 1) transplantation. 89 MPUC without history of organ transplantation and overall 755 UC (including cases with variant histology) were LTag negative. Of the five LTag expressing UC, three were MPUC, one showed extensive divergent differentiation with Mullerian type clear cell carcinoma, and one displayed focal villoglandular differentiation. All five tumors had aberrant nuclear p53 expression, 2/5 were HER2-amplified, and 3/5 had TERT promoter mutations. Within the 50 most common cancer related genes altered in UC we detected very few alterations and no TP53 mutations. BKPyV-DNA was present in 5/5 UC, chromosomal integration of the BKPyV genome was detectable in 4/5 UC. Two UC with BKPyV integration showed small deletions in the BKPyV noncoding control region (NCCR). The only UC without detectable BKPyV integration had a high viral load of human herpesvirus 6 (HHV-6). Our results suggest that LTag expression of integrated BKPyV genomes and resulting p53 inactivation lead to aggressive high-grade UC with unusual, often micropapillary morphology.
CRIS-Team WoS Importer:2020-02-28

Viral infections in gynaecology – recent developments in human papillomavirus and herpesvirus infections Virusinfektionen in der Gynäkologie – Aktuelle Entwicklungen bei humanen Papillomviren und Herpesviren - Nagel, Angela; Knöll, Antje (Pädiatrische Praxis, 2022)
Summary: Human papillomavirus (HPV) and herpes simplex virus (HSV) infections are the most common sexually transmitted viral diseases. Prophylactic measures such as HPV vaccination and behavioural precautions for genital herpes are the most promising strategies to prevent these viral infections. The HPV vaccine is safe, immunogenic and effective in the prevention of HPV-associated tumors, but the vaccination rate is far too low in Germany. Cervical cancer is comparatively rare in Germany today and the incidence rate of new cases has been stagnating at a low level for years. Since a persistent hrHPV infection is necessary for the development of cervical cancer, the cervical cancer screening program was modified in January 2020. For women aged 35 years and older, an HPV cervical smear test is now performed in addition to cytology and the screening interval has been extended to three years. The test algorithm for younger women has not been changed. For genital HSV infections, aciclovir-based therapy regimens are recommended, prophylactic or therapeutic vaccines will not be available in the near future. Therefore, information of the patient about the specifics of the disease (such as the often asymptomatic virus shedding) and initiation of an appropriate therapy are decisive for the reduction of the HSV transmission risk and for the treatment success.
CRIS-Team Scopus Importer:2024-12-16
Keywords: cervical carcinoma screening; genital infections; herpes simplex virus; HPV vaccine; human papillomavirus

Virusinfektionen in der Gynäkologie - Aktuelle Entwicklungen bei humanen Papillomviren und Herpesviren - Nagel, Angela; Knöll, Antje (gynäkologische praxis, 2020)
Human papillomavirus (HPV) and herpes simplex virus (HSV) infections are the most common sexually transmitted viral diseases. Prophylactic measures such as HPV vaccination and behavioural precautions for genital herpes are the most promising strategies to prevent these viral infections. The HPV vaccine is safe, immunogenic and effective in the prevention of HPV-associated tumors, but the vaccination rate is far too low in Germany. Cervical cancer is comparatively rare in Germany today and the incidence rate of new cases has been stagnating at a low level for years. Since a persistent hrHPV infection is necessary for the development of cervical cancer, the cervical cancer screening program was modified in January 2020. For women aged 35 years and older, an HPV cervical smear test is now performed in addition to cytology and the screening interval has been extended to three years. The test algorithm for younger women has not been changed. For genital HSV infections, aciclovir-based therapy regimens are recommended, prophylactic or therapeutic vaccines will not be available in the near future. Therefore, information of the patient about the specifics of the disease (such as the often asymptomatic virus shedding) and initiation of an appropriate therapy are decisive for the reduction of the HSV transmission risk and for the treatment success.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Cervical carcinoma screening; Genital infections; Herpes simplex virus; HPV vaccine; Human papillomavirus